Application of MootralTM Reduces Methane Production by Altering the Archaea Community in the Rumen Simulation Technique - Eger, Melanie; Graz, Michael; Riede, Susanne; Breves, Gerhard (Frontiers in Microbiology, 2018)
The reduction of methane emissions by ruminants is a highly desirable goal to mitigate greenhouse gas emissions. Various feed additives have already been tested for their ability to decrease methane production; however, practical use is often limited due to negative effects on rumen fermentation or high costs. Organosulphur compounds from garlic (Allium sativum) and flavonoids have been identified as promising plant-derived compounds which are able to reduce methane production. Here, we evaluated the effects of a combination of garlic powder and bitter orange (Citrus aurantium) extracts, Mootral, on ruminal methane production, ruminal fermentation and the community of methanogenic Archaea by using the rumen simulation technique as ex vivo model. The experiment consisted of an equilibration period of 7 days, an experimental period of 8 days and a withdrawal period of 4 days. During the experimental period three fermenters each were either treated as controls (CON), received a low dose of Mootral (LD), a high dose of Mootral (HD) or monensin (MON) as positive control. Application of Mootral strongly reduced the proportion of methane in the fermentation gas and the production rate of methane. Moreover, the experimental mixture induced a dose-dependent increase in the production rates of several short chain fatty acids and in the molar proportion of butyrate. Some effects persisted during the withdrawal period. Both, single strand conformation polymorphism and Illumina MiSeq 16S rRNA amplicon sequencing indicated an archaeal community distinct from CON and MON samples in the LD and HD samples. Among archaeal families the percentage of Methanobacteriaceae was reduced during application of both doses of Mootral. Moreover, several significant differences were observed on OTU level among treatment groups and after withdrawal of the additives for LD and HD group. At day 14, 4 OTUs were positively correlated with methane production. In conclusion this mixture of garlic and citrus compounds appears to effectively reduce methane production by alteration of the archaeal community without exhibiting negative side effects on rumen fermentation.